2017
DOI: 10.1007/s00775-017-1453-4
|View full text |Cite
|
Sign up to set email alerts
|

High cytotoxicity of vanadium(IV) complexes with 1,10-phenanthroline and related ligands is due to decomposition in cell culture medium

Abstract: Cytotoxic effects of Metvan (cis-[VO(OSO)(Mephen)], where Mephen = 4,7-dimethyl-1,10-phenanthroline) and its analogues with 1,10-phenanthroline (phen) and 2,2'-bipyridine (bpy) ligands in cultured human lung cancer (A549) cells have been re-investigated in conjunction with reactivity of the V(IV) complexes in neutral aerated aqueous solutions and in cell culture medium. All the V(IV) complexes underwent rapid oxidation to the corresponding V(V) species (cis-[V(O)L]), followed by release of free ligands (shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 58 publications
1
43
0
Order By: Relevance
“…On the other hand, some authors have reported the anticancer properties of vanadium and showed that complexes of these metals are the new metal-based drugs used in the treatment of several cancers, such us lung cancer 43 . Other authors have demonstrated the influence of vanadium compounds in the cytotoxicity of some ligands in human lung cancer cultured cells 44 .…”
Section: Elements Concentrations and Proposal Of Lung Cancer Biomarkersmentioning
confidence: 99%
“…On the other hand, some authors have reported the anticancer properties of vanadium and showed that complexes of these metals are the new metal-based drugs used in the treatment of several cancers, such us lung cancer 43 . Other authors have demonstrated the influence of vanadium compounds in the cytotoxicity of some ligands in human lung cancer cultured cells 44 .…”
Section: Elements Concentrations and Proposal Of Lung Cancer Biomarkersmentioning
confidence: 99%
“…However, it was also shown that the ligands themselves generate a similar toxicity profile in MTT assays of leukaemia cells [ 37 ]. Furthermore, it has now been shown that Metvan dissociates in cell culture medium to release vanadium and free 1,10-phenanthroline (phen) ligands [ 38 , 39 ]. Treatment with these phen ligands alone results in similar cytotoxicity in a lung cancer cell line (A549) compared to the whole Metvan complex.…”
Section: Vanadiummentioning
confidence: 99%
“…These ligands can also complex with copper and iron in the media, leading to enhanced cellular uptake, where they increase ROS production, ultimately leading to cell death [ 40 ]. Systemic toxicity associated with phen ligand has also been demonstrated in vivo [ 38 , 41 ]. Therefore, vanadium compounds containing such ligands are unlikely to be suitable for therapeutic applications directed solely at PTP enzymes themselves.…”
Section: Vanadiummentioning
confidence: 99%
“…However, a wide range of activities have been reported depending on the protein, biological system or specific vanadium species (Crans, 2000 ; Crans et al, 2013 ; Correia et al, 2015 ; Postal et al, 2016 ). Recently, it has become clear that compound uptake is critical to the mode of action because many vanadium compounds are modified during the uptake process (Pessoa and Tomaz, 2010 ; Crans et al, 2011 ; Le et al, 2017 ; Levina et al, 2017a ). In the case of a large anion such as decavanadate, the question is simply whether the species is too large to enter through protein channels and thus must be taken up through endocytosis or passive transport mechanisms.…”
Section: Introductionmentioning
confidence: 99%